Morphology of Kisaran City: The Circulation System in Urban Transformation 1929-2022 - Darmawan, Muhammad Yoki; Wibisono, Bambang Hari (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
The rapid economic growth and significant urbanization in Kisaran City have posed several challenges in urban planning, including adequate housing, health facilities, education, and transportation. The city's development was also influenced by its colonial history, with the dominance of colonial power regulating the production and trade of plantation products as well as the lives of local people. The morphological transformation of the city from 1929 to 2022 reflects the challenges related to infrastructure, visual appearance, and the growth of the commercial sector, which have affected the lives of citizens and demanded the city's adaptation to the development of the times. Historical events, such as colonization by foreign powers and Chinese immigration, have affected the population growth of Kisaran and caused pressure on infrastructure and socio-economic inequality. This study aims to understand the morphology of Kisaran City and the factors that influence its transformation by using the methods of literature study, synchronic approach, and diachronic approach. The results of the study concluded that the morphological transformation of Kisaran City was influenced by the circulation system, which adapted to the needs and trends of society, and interacted with each other in forming the morphology of Kisaran City that continues to develop over time.